Meeting the Challenge of Providing Nutrition Services During the COVID-19 Pandemic. - Kolasa, Kathryn M.; Craven, Kay; Nordby, K. (My University, 2021)
Examples of Registered Dietitian Nutritionists (RDNs) who used their abilities to innovate and adapt to ensure the public, their patients and clients received continuous nutrition services, weight management services, diabetes prevention programs and Medical Nutrition Therapy during the lock-down of many "non essential" medical services during COVID 19. Strategies used in outpatient practices, Cooperative Extension Service and public health agencies are described.
Contributions came from Lindsay Drier MS, RDN, LDN; Kathleen Ascanio MS, RDN, LDN; Robin Tant MPA, RDN, LDN; Ashley Strickland RDN, LDN, CNSC; Laura Matarese PhD, RDN, LDN, CNSC, FADA, FASPEN, FAND; Jill Jennings MS, RDN, LDN and Julia Johnstone MS, RDN, LDN
Keywords: COVID 19, diabetes prevention programs, nutrition education, nutrition services